2019
DOI: 10.1155/2019/4291689
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiles of Peripheral Blood Monocytes in Osteoarthritis and Analysis of Differentially Expressed Genes

Abstract: Background There is little understanding of the molecular processes involved in the pathogenesis of osteoarthritis, limiting early diagnosis and effective treatment of OA. Use of genechips can provide insights into the molecular pathogenesis of diseases. In this study, determination of gene expression profiles of osteoarthritis peripheral blood mononuclear cells will allow exploration of the molecular pathogenesis of OA and find out more candidate biomarkers and potential drug targets of OA. Result A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Conversely, some well-known factors such as NFATC1, SPI1 , and FOSL2 were upregulated in the process (Fig. 4f ), which are involved in regulating differentiation, survival and size of OC 37 , 38 . We also found some unidentified regulators such as JDP2, ZNF267, CAMTA2, MLX, HES4, and GLMP in OS lesions, which are potentially engaged in the cellular transition from the myeloid monocytes into mature OC cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, some well-known factors such as NFATC1, SPI1 , and FOSL2 were upregulated in the process (Fig. 4f ), which are involved in regulating differentiation, survival and size of OC 37 , 38 . We also found some unidentified regulators such as JDP2, ZNF267, CAMTA2, MLX, HES4, and GLMP in OS lesions, which are potentially engaged in the cellular transition from the myeloid monocytes into mature OC cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…ese hubs were shown to be involved in the regulation of pain-related processes and could function as potent targets to induce analgesic effects. e PIK3R1 gene was suggested to have the potential to function as a painrelated regulator according to the genetic interaction analysis [133], and its expression level might be associated with osteoarthritis pathogenesis [134]. Upregulation of the HSP90AA1 gene was observed in patients with fibromyalgia [135][136][137], and pharmacological inhibition of heat shock protein 90 (HSP90; encoded by HSP90AA1) was shown to alleviate monoarthritis-induced pain [138].…”
Section: Network Pharmacology-based Analysis Of Jakyak-gamchomentioning
confidence: 99%
“…the evaluation and control of the quality of traditional Chinese medicine must truly reflect its "internal" and "comprehensive" quality [26]. [30]; and its expression level may be related to the pathogenesis of osteoarthritis [31];…”
Section: Discussionmentioning
confidence: 99%
“…inflammatory reaction and regulate immune function to treat CS. According to the analysis of genetic interaction; PIK3R1 gene is considered to have a potential pain-related regulatory function [30]; and its expression level may be related to the pathogenesis of osteoarthritis [31]; which lays a foundation for the pharmacological effect of JFKG on promoting blood circulation and relieving pain. Pharmacological data in previous research showed that PI3K-Akt signal pathway can promote angiogenesis and promote blood flow by activating important vasoactive factors such as vascular endothelial growth factor and nitric oxide [32][33].…”
Section: Discussionmentioning
confidence: 99%